Energy Efficient Routing Protocol Design for Wireless Networks: Enhancing the Lifetime of Wireless Sensor Networks with Energy Efficient Routing Protocols (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Nowadays the Wireless Sensor Network in gaining the importance in daily working or in different industries. The WSN is mostly used in communication and energy related industries. The Sensor Nodes are sense the data and information. Then it is process the sensed data to transfer this data and information to base station using radio frequency (RF) channel. This technology is important in the monitoring and tracking system. To improving the life of sensor and battery, it is necessary to scheme energy efficient routing protocol which can eliminate the entire problems that decreases the efficiency of WSNs. This innovation paper represent that several problems associated to energy efficient routing protocol for WSNs. If any node runs out of power, the entire network connectivity collapses and intend of the deployment might become futile. Because of this reason most of the research in the area of WSNs has concentrated on energy efficiency where the design of energy efficient routing protocols plays a major role. This research work titled “Energy Efficient Routing Protocols for Wireless Sensor Networks” proposes to implement energy efficient routing vii protocol scheme so as to enhance the lifetime of the WSNs.